The Relationship Between Intimate Partner Violence and PTSD in Women Survivors and the Influence of Risk Factors: A Systematic Literature Review (British Journal of Multidisciplinary and Advanced Studies, 2024)
Post-Traumatic Stress Disorder (PTSD) is associated with traumatic experiences stemming from traumatic situations such as war conflicts, accidents and natural disasters, while it thrives in abusive situations. In the context of partner relationship abuse, female survivors make up a high proportion of people with PTSD. This systematic literature review aims to investigate the relationship between PTSD and Intimate Partner Violence (IPV) in female survivors and examine the risk factors which may play a role in the development of PTSD in women IPV survivors. Following the PRISMA 2020 writing protocol, this study collected research in order to present the impact of Intimate Partner Violence on PTSD. The findings highlighted a positive correlation between partner violence and PTSD and between PTSD and risk factors such as brain injury, low self-confidence, history of child abuse, negative social reactions, lack of resources and insecure attachment bonds. The negative consequences of Intimate Partner Violence manifest both on women's mental and physical health and there is often comorbidity between mental disorders such as depression, and physical health problems such as chronic pain and injuries.